Financial Sector Assessment Program Update : Saudi Arabia - The IOSCO Objectives and Principles of Securities Regulation - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
The regulatory framework for the securities market in Saudi Arabia has significantly developed since the enactment of legislation to regulate the capital markets. The Capital Market Authority (CMA) has made significant progress in establishing its supervision credentials, including issuing implementing regulations. The CMA has also entered into information sharing arrangements with other regulators in the region, and is a party to the International Organization of Securities Commissions (IOSCO) Multilateral Memorandum of Understanding (MMOU) Concerning Consultation and Cooperation and the Exchange of Information. However, no information sharing arrangement exists with the Saudi Arabian Monetary Agency (SAMA). Even so, refinements can be made to processes, the Capital Market Law (CML), and the Committee for the Resolution of Securities Disputes (CRSD). The framework contained in the CML and the implementing regulations is still relatively new. However, revision and updating of the requirements needs to be a continuing program, involving fuller regulated entity participation. The assessment is part of the financial sector assessment program update made at the request of Saudi Arabia, and is the first assessment conducted of the implementation of the IOSCO objectives and principles of securities regulation.